ANALISIS KINERJA BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM PENANGGULANGAN BENCANA BANJIR DI KOTA SEMARANG - Syafril, Sinta; Sulandari, Susi (Journal of Public Policy and Management Review, 2019)
Indonesia is one of the countries prone to floods. The city of Semarang is one of the cities frequently affected by floods and gets third place in Central Java Province. The Semarang City Disaster Management Agency (BPBD) is the body responsible for handling disasters that occur in the city of Semarang. The purpose of this study was to analyze and describe the performance of the Regional Disaster Management Agency (BPBD) as well as the driving and inhibiting factors in flood management. The research method used is descriptive qualitative method. The indicators used to assess the performance in this study were productivity, service quality, responsibility, and accountability. In addition, it is also seen from the driving factors and inhibitors the organizational performance. The results of the study showed that the productivity of the performance in flood management has not been optimal, because there were still programs or activities that have not reached the target. The service quality in flood management has not been maximized and needs to be improved, the responsibility carried out is quite good but there are still obstacles, and not yet accountable and transparency to the community. Factors that hinder performance were lack of reliable and skilled human resources in their field, lack of facilities and infrastructure, limited funds, lack of coordination with various stakeholders, while leadership, and team were the drivers. The recommendation of researchers was to improve the skills and abilities of employees through training, improve facilities and infrastructure, improve coordination with various stakeholders and adjust the priorities of flood disaster management programs with a budget ceiling.